Exploring the comparative cardiovascular death benefits of sodium–glucose cotransporter 2 inhibitors in type 2 diabetes: a frequentist and Bayesian network meta-analysis-based scoring - Ghosal, Samit; Sinha, Binayak (Frontiers in Endocrinology, 2023)
Background and aims: Cardiovascular death (CV death) is the most objective component of the primary or secondary end point components in cardiovascular outcome trials (CVOTs) conducted with sodium glucose cotransporter 2 inhibitors (SGLT-2is). CV death features clubbed with two types of primary composite outcomes, with major adverse cardiovascular events (MACE) in trials with atherosclerotic cardiovascular disease (ASCVD) at baseline or with CV death or hospitalization for heart failure (hHF) with heart failure at baseline. Unlike the primary composite, CV death reduction demonstrated significant variations among the CVOTs with SGLT-2is. Moreover, the impact of the individual agents within the SGLT-2is group on reduction in CV death have not been explored objectively. This network meta-analysis was undertaken to construct a hierarchy based on indirect pairwise comparisons and rankings among the individual agents within SGLT-2is. Methods: A Cochrane library-based web search yielded 16 randomized controlled trials for analysis. Stata/BE 17.0 and RStudio 2022.07.1 Build 554 software were used to conduct a frequentist as well as a Bayesian network meta-analysis. The effect size was assessed based on the risk ratio (RR). Ranking the individual agents was done with the frequentist approach (P-score and the MDS [multidimensional scaling] rank system) and the Bayesian ranking (Surface Under the Cumulative Ranking [SUCRA]). Results: Regarding the overall data, SGLT-2is reduced CV death risk by 12% (RR:0.88, 95% CI 0.80-0.96). All the three scoring resulted in empagliflozin scoring the highest. There was a 15% RR reduction in CV death (95% CI 0.71-1.02) in the ASCVD or multiple cardiovascular risk factor (MRF) group and a 11% RR reductio the HF group, with empagliflozin ranking the highest in the former group and dapagliflozin in the later. Conclusions: Empagliflozin ranked the highest compared to the other SGLT-2is in the overall population and the trials including T2D patients with ASCVD or MRF at baseline, while dapagliflozin ranked the highest in the trials with HF at baseline.